Periapical Microsurgery with an Endoscope and Microscope of Two Upper Central Incisors Already Subjected to Periapical Surgery 25 Years Ago - Pablo Glera-Suarez; Blanca Serra-Pastor; David Peñarrocha-Oltra; Miguel Peñarrocha-Diago; Cosme Gay-Escoda (Case Reports in Dentistry)
Introduction. The present clinical case describes periapical microsurgery with an endoscope and microscope in a patient already treated 25 years ago due to persistent periapical disease of the two central upper incisors, restored with poorly adapted crowns. Clinical Case. The first periapical surgery had been performed with silver amalgam as a retrograde filler material, causing grayish staining of the buccal mucosa. Periapical surgery was performed raising a submarginal flap with ostectomy and apicoectomy, retrograde cavity preparation with ultrasound tips, and filling with mineral trioxide aggregate (MTA). After soft tissue healing and complete bone regeneration of the lesion, retreatment of the incisors with a fixed prosthesis was carried out, adopting the biologically oriented preparation technique (BOPT). Conclusions. The described periapical microsurgery approach with magnification and illumination of the surgical field was found to be effective, avoiding the need to extract the two central upper incisors.